Brazilian plants urgently needing conservation: the case of Vriesea minarum (Bromeliaceae) - Versieux, Leonardo M. (Phytotaxa, 2011)
Difficulties in identifying Vriesea minarum as well as a conflict of interest among mining companies and local conservationists are pushing this species towards extinction. Vriesea minarum was categorised as data deficient in the Brazilian official plant red list despite earlier works indicating its vulnerability. This species is restricted to the Iron Quadrangle area, Minas Gerais, Brazil, where it grows over iron rock outcrops. Here we use V. minarum to illustrate the importance of taxonomic investigation as well as the presentation of accurate distributional data in order to establish conservation strategies. We emphasize the importance of well-conserved herbaria collections and adequate type material to avoid taxonomic issues that delay the understanding of species limits. This paper presents taxonomic notes and the redefining of V. minarum based on the survey of 22 herbaria collections and fieldwork. The additional material obtained and a morphometric approach allowed us to better delimit the related taxa. The species V. ouroensis is considered to be a new synonym of V. minarum. A map showing the occurrences of populations of V. minarum, pictures of living specimens in the field, as well as its updated conservation status are provided. Historic records housed in herbaria indicate that this species has been progressively losing its area of occurrence.